Spectral OCT-Angiography in En Face Mode for Detection of Morphological Changes in the Retinal Pigment Epithelium before and after Selective Micro-Pulse Laser Exposure in Patients with Central Serous Chorioretinopathy - P. L. Volodin; E. V. Ivanova; E. Iu. Polyakova; A. V. Fomin (Oftalʹmologiâ)
Purpose — to study the morphological changes of the retinal pigment epithelium (RPE) by optical coherence tomography-angiography (OCT-A) in En Face mode before and after selective micropulse laser irradiation in patients with central serous chorioretinopathy (CSC), determine the correspondence between the topographic location of RPE defects and detachment on the OCT-angiogram in En Face mode and points of leakage on the FAG.Patients and methods. There were 20 patients (21 eyes) with CSC before and after laser treatment under the observation. All patients underwent high-resolution FAG and OCT-A using Angio Retina 2×2 or 3×3 mm protocol and Angio Retina HD 6×6 mm. The treatment was carried out in a selective micropulse mode with individual selection of parameters using the Navilas 577s navigation laser system (OD-OS, Germany) or the IQ 577 laser system (IRIDEX, USA).Results were evaluated at 2 weeks and 1 month after treatment. Results. In all cases, the leaking points of the subretinal fluid on FAG corresponded to the topographic location of defects and detachments of RPE detachment on OKT-A En Face. According to OCT-A En Face, the following morphological changes were revealed: in 5 cases — single defects of RPE, in 7 cases — multiple defects of RPE, in 9 cases of slit-like detachment of RPE, in 3 patients a combination of slit-like detachment and defect RPE. The sizes of RPE defects varied in the range from 21 to 159 microns, while their rounded shape prevailed. 1 month after the selective micropulse laser effect on OCT-A in the En Face mode, the defects were closed and the RPE detachments fit in all patients, which resulted in resorption of the subretinal fluid and the neurosensory retina attachment.Findings. OCT-A in En Face mode is a highly informative diagnostic method that allows noninvasive detection of morphological changes in RPE with a clear topographic localization relative to the retinal vascular network, as well as evaluating the effectiveness of selective micropulse laser treatment in patients with CSC.